2017
DOI: 10.1039/c7ra09435c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu–Mg/ZnO catalysts and catalysis in dimethyl oxalate hydrogenation to ethylene glycol: enhanced catalytic behavior in the presence of a Mg2+ dopant

Abstract: Mg2+ doped nanoscale Cu–Mg/ZnO catalysts prepared by the co-precipitation method have been systematically characterized focusing on the amount of Mg2+ ions incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Furthermore, Chen, et al. reported that the Cu‐1Mg/ZnO catalyst with 1 wt% MgO loading synthesized from pure malachite phase structure significantly improved the dispersion status of Cu, which effectively promoted dimethyl oxalate hydrogenation to ethylene glycol . The theoretical explanations of the experimental observations are provided in the present work where the consequences of incorporation of Mg in Cu/Zn malachite has been studied in detail and the crucial observations in brief are as follows, (a) introducing Mg into malachite structure improves the structural stability, (b) relatively higher substitution ratio of Mg/Zn into malachite promotes better Cu dispersion status and (c) relevant electronic environments of Cu/Zn will be modified by the incorporation of Mg atoms, which affects their reducibility.…”
Section: Resultsmentioning
confidence: 64%
“…Furthermore, Chen, et al. reported that the Cu‐1Mg/ZnO catalyst with 1 wt% MgO loading synthesized from pure malachite phase structure significantly improved the dispersion status of Cu, which effectively promoted dimethyl oxalate hydrogenation to ethylene glycol . The theoretical explanations of the experimental observations are provided in the present work where the consequences of incorporation of Mg in Cu/Zn malachite has been studied in detail and the crucial observations in brief are as follows, (a) introducing Mg into malachite structure improves the structural stability, (b) relatively higher substitution ratio of Mg/Zn into malachite promotes better Cu dispersion status and (c) relevant electronic environments of Cu/Zn will be modified by the incorporation of Mg atoms, which affects their reducibility.…”
Section: Resultsmentioning
confidence: 64%
“…The high-temperature peak is attributed to the reduction of CuO particles interacting with ZnO. 29 The increase in reduction temperature after doping with Mg or La is ascribed to the strengthened interaction between Cu and the doped ZnO. The greatest increase in highest reduction temperature is observed for La-doped CZA (CZA: 260 °C, Mg-CZA: 268 °C, La-CZA: 286 °C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mg is an isoelectronic ZnO dopant with a similar ionic radius. Mg was doped into ZnO to regulate its (i) electronic structure, (ii) surface oxygen defect, and (iii) metal–support interaction, , without affecting the morphology of ZnO. Similarly, La is an effective electronic promoter for introducing defects into ZnO without imposing significant morphological changes at a controlled level of doping .…”
Section: Introductionmentioning
confidence: 99%
“…It is the world's second largest nutritional supplement for crops after nitrogen (Adnan et al, 2017). Mg and its compounds are widely used in a number of high-value industrial applications such as in the production of certain alloys and catalysts, and in the chemical, electronic, pharmaceutical and agricultural industries (Tran et al, 2013;Tran et al, 2016;Kong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%